Phlebotomine fauna (Diptera, Psychodidae) in parks of the City of São Paulo, State of São Paulo, Brazil - de Oliveira Castelo, Neide de Oliveira Castelo (2015)
Leishmaniases are anthropozoonoses whose agents are transmitted by the bite   of females of several species of sand flies. Human population growth and   environmental change have contributed to the increase in cases of utaneous   and visceral leishmaniases in the State of São Paulo. This study aimed to   survey the sand fly fauna in the parks of São Paulo municipality. Samples   were collected in eight parks: Alfredo Volpi, Anhanguera, Burle Marx,   Cantareira, Carmo, Chico Mendes, Ecológico Tietê and Fundação Parque   Zoológico (Zoo), using New Jersey (NJ) and / or Center for Disease Control   (CDC) light traps, installed weekly between 2004 and 2011. A total of 20,828   sand flies - 16,883 females (81%) and 3,945 males (19%), were collected   belonging to 24 species and 11 genera: Brumptomyia (6), Evandromyia   (1), Expapillata (1), Lutzomyia (1), Martinsmyia (1), Micropygomyia   (1), Migonemyia (1), Nyssomyia (2) Pintomyia (3) Psathyromyia (4) and   Psychodopygus (3).The Cantareira park presented the highest species richness   (22) and the largest number of specimens collected (3,904 in CDC and 12,047   in NJ). Pintomyia fischeri and Psathyromyia pascalei occurred in all the   parks, the former was the most prevalent species in Cantareira, Alfredo Volpi,   Carmo and Zoo parks. Evandromyia edwardsi was the most frequent species   in the Burle Marx park. Pi. fischeri, Mg. migonei, Ny. intermedia and Ny.   whitmani, implicated as vectors of Leishmania (V.) braziliensis, were found   in Anhanguera, Cantareira, Carmo, Chico Mendes and Zoo parks.